2022
DOI: 10.2217/fon-2021-1379
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of Soluble TIM-3 in Oral Squamous Cell Carcinoma

Abstract: Objective: To evaluate the soluble TIM-3 (sTIM-3) expression level in oral squamous cell carcinoma (OSCC) and determine its clinical diagnostic potential. Methods: The sTIM-3 and squamous cell carcinoma antigen (SCCAg) levels of 199 OSCC patients and 107 healthy individuals were assessed using an enzyme-linked immunosorbent assay and their individual and combined efficiency rates were compared. Results: The results showed higher sTIM-3 and SCCAg levels in the OSCC patients and better diagnostic potential for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Most studies that have evaluated sTIM3 levels have found them to be higher in cancer patients compared to healthy donors, with increased levels observed specifically in patients with NSCLC [104], hepatocellular carcinoma [148], oral squamous cell carcinoma [149], differentiated thyroid carcinoma [56], basal cell carcinoma [57], gastric cancer [150], and osteosarcoma [151]. Only two studies have reported lower levels of sTIM3, both in patients with early breast cancer, compared to those of healthy donors [66,67], while two others found no difference in the levels between healthy donors and patients with nasopharyngeal carcinoma [55,65].…”
Section: Stim3 Expression In Cancer Patient Plasma/serum and Associat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies that have evaluated sTIM3 levels have found them to be higher in cancer patients compared to healthy donors, with increased levels observed specifically in patients with NSCLC [104], hepatocellular carcinoma [148], oral squamous cell carcinoma [149], differentiated thyroid carcinoma [56], basal cell carcinoma [57], gastric cancer [150], and osteosarcoma [151]. Only two studies have reported lower levels of sTIM3, both in patients with early breast cancer, compared to those of healthy donors [66,67], while two others found no difference in the levels between healthy donors and patients with nasopharyngeal carcinoma [55,65].…”
Section: Stim3 Expression In Cancer Patient Plasma/serum and Associat...mentioning
confidence: 99%
“…Among cancer patients, higher sTIM3 has consistently been reported (in seven different studies) to associate with a higher histological tumor grade/stage of cancer. This is true in NSCLC [104], hepatocellular carcinoma [152], oral squamous cell carcinoma [149], gastric cancer [150], clear cell renal cell carcinoma [153], and osteosarcoma [151]. Higher sTIM3 also correlated with a larger tumor size and the presence of distant metastases in patients with osteosarcoma [151], and with larger tumor size, later TNM stage, and the presence of cervical lymph node metastases in patients with differentiated thyroid carcinoma [56].…”
Section: Stim3 Expression In Cancer Patient Plasma/serum and Associat...mentioning
confidence: 99%